Comparison Analysis of the Implementation of Indonesia and Finlad Education Policies - Rizki Ananda; Natasya Nazirah; Dea Rona Sapitri; Elsa Riani (Universitas Muhammadiyah Enrekang, 2023)
This study aims to find out how to compare the application of education in Indonesia with education in Finland. Education in Indonesia is very far behind compared to education in other countries. Finland as one of the countries with the best education system has become a reference for the implementation of education in countries in the world. In contrast to Indonesia, the comparison of education looks very much different. The research method used is a literature review, where data is collected from various sources such as journals or books that have been analyzed based on existing problems. There are several differences regarding education between the two countries, namely, 1) Indonesian education is more widely used for competency events, whereas Finland prioritizes the principle of equality, 2) there is a class-resident system for students whose abilities are below average and student rankings, Finland does not use a system like this, 3) Indonesia has a weekly study load of +/- 40 hours, Finland studies +/- 30 hours per week, 4) in Indonesia, learning is mostly done in classrooms, while Finland uses problem-solving methods, 5) assignments will always be there every time they meet face to face for students in Indonesia but not for Finland, this country does not burden students to do the task. And finally, 6) teachers in Indonesia can be at least D4, in Finland the teacher qualifications are at least a master's (S2). With an increase in the quality of teachers,